GEOCHEMICAL EVALUATION OF KHUMNOH LIMESTONE, KASHMIR, INDIA: IMPLICATIONS FOR CEMENT INDUSTRY AND SUSTAINABLE RESOURCE UTILIZATION - Gazala Yousuf Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The Khumnoh limestone deposits of Kashmir, situated within the tectonically active northwestern Himalayas, hold significant economic potential for the cement industry. However, a comprehensive geochemical and mineralogical evaluation is essential to ascertain their suitability for industrial applications. This study integrates major and trace element geochemistry, petrographic analysis, and industrial feasibility assessments to characterize the limestone’s composition, depositional history, and potential for clinker production. A total of eight representative limestone samples were systematically collected and subjected to X-ray fluorescence (XRF), X-ray diffraction (XRD), and petrographic investigations. The geochemical analysis reveals that the CaO content ranges from 50.12% to 54.89%, with low SiO₂, Al₂O₃, and Fe₂O₃ concentrations, indicating high chemical purity. The trace element profiling exhibits minimal Mn, Sr, and P₂O₅, further enhancing its desirability for cement manufacturing. Petrographic observations confirm the dominance of fine- to medium-grained calcite with minor dolomitization and siliceous impurities, suggesting a shallow marine depositional environment with diagenetic overprinting. The findings demonstrate that the Khumnoh limestone meets international cement-grade standards (ASTM C150, BIS 4032-2022), positioning it as a viable raw material for clinker production. However, localized variations in siliceous and argillaceous intercalations necessitate beneficiation strategies to optimize its industrial utility. The study also underscores the imperative of sustainable extraction practices, given the region’s geological sensitivity and ecological constraints.This research provides a scientific framework for resource evaluation, industrial application, and sustainable utilization of the Khumnoh limestone. The results hold critical implications for cement manufacturing, regional economic development, and strategic raw material management in the Himalayan domain.